Inhibition of Itch by Hunger and AgRP Neuron Activity. (1st December 2020) - Alhadeff, Amber L.; Park, Onyoo; Hernandez, Elen; Betley, J. Nicholas
Highlights: Hunger inhibits itch induced by multiple pruritogens. Increased hunger levels correlate with a more potent inhibition of itch response. Hunger sensitive hypothalamic AgRP neurons are sufficient to mediate the suppression of itch. Hunger, via AgRP neuron activity, intricately prioritizes physiological need states. Abstract: Unpleasant somatosensory stimuli such as pain and itch can interrupt normal behavior. But survival can depend on resuming normal behavior before these challenges are fully resolved. The neural mechanisms that prioritize behavior when individuals are challenged with unpleasant somatosensory sensations, however, are not fully understood. Recently, we identified a neural circuit activated by hunger that can inhibit pain, prioritizing food seeking over tending to an injury. Here, we examine the ability of hunger, and neurons activated by hunger, to inhibit behavioral responses to another unpleasant somatosensory sensation – itch. We demonstrate that food deprivation inhibits scratching induced by three different pruritogenic stimuli: histamine, serotonin, and chloroquine. The inhibition of scratching correlates with the level of food deprivation, suggesting a cross-competition of alarm systems in the brain whereby more energy need more efficiently inhibits competing drives. Finally, we show that activity in hunger-sensitive, hypothalamic agouti-related protein (AgRP)-expressing neurons is sufficient to inhibit itch. Taken together, we showed that hunger or AgRP neuron activity inhibits itch, demonstrating that organisms have neural systems to filter and process ascending spinal signals activated by unpleasant somatosensory stimuli to prioritize salient needs.